Factors Affecting Indonesian Students’ Achievements in the International TIMSS Study - Syaifuddin, Mohammad; ., . (International Journal of Engineering and Technology, 2019)
This research examined the structural equation model of relationships between the studentsâ€™ mathematics achievement and socio-educational factors (family background, beliefs, instruction, school environment, teachers, and the studentsâ€™ attitudes) and investigated the direct and indirect effect of the factors that influenced the studentsâ€™ mathematics achievement in Indonesia. The samples were 5762 eighth grade students of Junior High School of the TIMSS study 2003. There were 7 research variables, with 5 exogenous variables (family background, beliefs, instruction, school environment, and teachers), and 2 endogenous variables (the studentsâ€™ attitudes and mathematics achievement), with 14 indicators. The data were taken from TIMSS study 2003. The data were analyzed using the path analysis with the generating model and using Lisrel 8.50 software. The criterion used to test the model was GFI ï‚³Â 0.95 or p > 0.05. The results of this research showed that (a) the structural equation model of the modification 2 - the influence of the family background, beliefs, instruction, school environment, teachers, and the studentsâ€™ attitudes to the studentsâ€™ mathematics achievements - fit with the empirical data; (b) the family background, instruction, school environment, teachers, and the studentsâ€™ attitudes had the direct effect on the studentsâ€™ mathematics achievements. Nevertheless, the school environment influenced the studentsâ€™ mathematics achievements conversely. The belief of students and instruction was not influential in a manner indirectly towards the studentsâ€™ mathematics achievements; and (c) the most significantly influential factors towards the studentsâ€™ mathematics achievements were the family background, instruction, and the teachers respectively.Â Â